A biomechanical analysis of the novice swimmer using the butterfly stroke - Togashi, T.; Nomura, T. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The purpose of this study was to clarify the technical characteristics of novice swimmers using the butterfly stroke. Twenty-five novice swimmers swam two 25 m maximal trials which were filmed by an underwater VTR camera. The velocity and angle of joints and segments were calculated by the Direct Linear Transformation (DLT) method using a microcomputer. Significant correlations were found between (1) elbow angle at catch point and average swimming velocity, (2) appearance time of high elbow and average swimming velocity, (3) fluctuations in horizontal velocity and average swimming velocity, (4) horizontal distance from entry point to release point and average swimming velocity. In conclusion, the high elbow technique and early appearance of high elbow at the catch point were considered very important for the correct butterfly stroke in novice swimmers.